(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In the traditional education management systems, records of current or former users are maintained by public or private organizations. And these records are in the institution or ministry that students attend or attended. And these records are maintained conventionally. If a user wants to transfer from one organization to another, the candidate’s records may transfer along with the organization, but some education records may remain at school or education department. Or when they apply for further delegation, the process of applying and verification of the certificate takes too much time. In the traditional education management system, every educational department maintains data with their own database for keeping the records. Now it is very difficult to know the complete previous or present record of a student in the different organizations. And if we want to, then we retrieve their entire data from their concern educational departments, which takes a lot of time. For better management, there are such software which are available in the market, but schools or institutions find it difficult to retrieve the exact information from the system and managing the system with tons of student records, technical management of the software and the more users makes the system more complicated. The purpose of this paper is to describe the design of a cloud base digitized academic system for improving current traditional education system.